Occupational safety and health administration practices and their effects on employee performance in Mavoko constituency within Machakos county ﻿ - Mwaruta, Selerina Samba (My University, 2013)
Occupational Safety and Health (OSH) is generally defined as the Science of the Anticipation, recognition, evaluation and control of hazards arising in or from the workplace that could impair the health and well-being of workers, taking into account the possible impact on the surrounding communities and the general environment. Some 160 million workers suffer from work-related diseases and about two-thirds of those are away from work for four working days or longer. After work-related cancers, circulatory diseases and certain communicable diseases, accidental occupational injuries are the fourth main cause of work-related fatalities. The main objective of this study was to evaluate the effect of Occupational Safety and Health Administration (OSHA) practices on employee performance of manufacturing firms located in Mavoko constituency within Machakos County. The researcher adopted an ex-post facto design where independent variables have "alreadyoccurred and are not manipulated by the researcher. Independent" variable will include occupational practices, safety practices and "health administration practices and the dependent variable will be employee performance. The target population of this study was drawn from all manufacturing forms in Mavoko constituency within Machakos County. The location was suitable for the study since there are many manufacturing firms within the constituency. The area is also accessible to the researcher. Purposive sampling was done where all OSHA officers in these organizations formed the sample attributable to the fact that they could easily articulate the issues under study. The study used semi-structured questionnaires and observation checklists to obtain relevant information. Piloting was done irfthree of the manufacturing firms so as to adjust the data,f collection tools if need be. The researcher together with three trained research assistants visited the manufacturing firms and administered the questionnaires to ~ respondents. They adopted a drop-and pick-later approach. Questionnaires were administered in the merning and collected in the evening or at a later date to allow the respondents enough time to fill the questionnaires. However, the checklist was filled by the researcher and the research assistants the same day. The data collected was coded and analyzed using statistical package for social sciences (SPSS) .version 17 computer package. The study findings revealed that occupational, safety and health administration practices have a positive effect on employee performance of manufacturing firms in Machakos County. There was a very strong positive relationship (R= 0.932) between the variables. The study also revealed that 86.9% of employee performance of manufacturing firms in Machakos County could be explained by the variables under study. However, occupational practices had more explanatory power on employee performance than the other practices. This was followed by safety practices and health administration practices respectively. The study findings were presented in form of tables and graphs